PENGARUH BUDAYA DAN PEMBELAJARAN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. NAV JAYA MANDIRI MATARAM - khaerul hadi; tina juniawati; topan siswanto (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
This study aims to assess and analyze the influence of culture and organizational learning simultaneously and partially on the performance of employees at PT. Nav Jaya Mandiri Mataram. This study consists of two (2) independent variables, namely culture (X1) and organizational learning (X2) and the dependent variable is the performance (Y). This type of research is associative research. Data collection techniques in this research is observation, interviews and questionnaires. The population in this study were permanent employees at PT. Nav Jaya Mandiri Mataram as many as 56 employees. The sampling technique in this research is the technique of random sampling with total sample of 36 people. The analytical tool used in this research is multiple linear regression. The results showed that proven organizational culture and learning simultaneously significant effect on the performance of employees at PT. Nav Jaya Mandiri Mataram with F count larger than F table that is 21.859> 3.28 with a significant probability of 0.022 <0.05. Based on t test showed that the culture and organizational learning proven partially significant effect on the performance of employees at PT. Nav Jaya Mandiri Mataram. The results also showed that the increase in performance of 64.7% employees are influenced by culture and a learning organization.